Que Nordeste é Este? Manguebeat, Intellectuals and Popular Music in the Making of the Brazilian Nordeste - Slater, Russell John (2019)
Since emerging as a geographic term at the beginning of the 20th Century, Brazil's "north-east" has grown to become a socioeconomic, political and cultural term tied to the region's subaltern position in a Brazilian hegemonic power structure defined by the south-east of the country. In the early 90s manguebeat emerged out of Recife (the traditional home of north-eastern Brazil) as a counter-hegemonic movement that also heralded new trends in Brazilian culture defined by contemporaneity, post-genre and urban multi-ethnicity. This thesis explores the manguebeat movement, making comparison with other historic and contemporary artists, intellectuals and movements from the local, national and international spheres. It traces the origins of the north-east (or "nordeste") as a cultural term, examining the literary and intellectual traditions of the region, including the region's musical contributions and the seminal works of its most noted intellectuals and writers of fiction. The thesis thus offers a portrait of Brazilian culture as seen from a subaltern region, and how contemporary movements are seeking to redefine the connotations of what it means to be "nordestino".